Effect of BaTiO3 additive on the electrical properties of Na0.50Bi0.50TiO3 lead free ceramics - Sharma, Dhananjay K.
The near morphotropic phase boundary (MPB) compositions of lead-free piezoelectric ceramics based on sodium bismuth titanate (Na0.50Bi0.50TiO3: NBT) and barium titanate (BaTiO3: BT) were carefully investigated by conventional high temperature mixed-oxide method. All the ceramics exhibit single phase rhombohedral symmetry. The frequency (100 Hz to 1 MHz) and temperature (Room temperature-500 degrees C) dependence of impedance spectroscopy of (1 - x)Na0.50Bi0.50TiO3-xBaTiO(3) (x = 0.0, 0.06, 0.07 and 0.08) ceramics were investigated by impedance analyzer. The frequency explicit plots of Z '' versus frequency at various temperatures show peaks in the higher temperature range (>400 degrees C). The compounds show dielectric relaxation, which is found to be of non-Debye type and the relaxation frequency shifted to higher side with increase in temperature. The activation energy values obtained for different BT content suggest that the electrical conduction in NBT is mainly due to the mobility of the ionized oxygen defects. (c) 2013 Elsevier B.V. All rights reserved.